Influence of extraction parameters on physico-chemical characters and antioxidant activity of water soluble polysaccharides from Macrocybe gigantea (Massee) Pegler & Lodge - Khatua, Somanjana (J Food Sci Technol, 2015)
Polysaccharides from mushrooms are potentially active pharmaceutical ingredients and their action is dependent upon conformation, composition, size etc. In this context, three water soluble crude polysaccharide rich fractions viz. hot water extracted polysaccharide (HWP), cold alkaline extracted polysaccharide (CAP) and hot alkaline extracted polysaccharide (HAP) have been isolated using varying extraction parameters from Macrocybe gigantea, a well-known edible mushroom collected from Gangetic plain of West Bengal and authenticated by DNA barcoding of nrDNA ITS region. Physico-chemical investigation revealed that the fractions were mainly composed of β-configuration in pyranose form of sugars conjugated with small amount of protein. Further analysis presented that polysaccharides were composed of same monosaccharide even in similar order of ratio (D-glucose > D-galactose > D-mannose > D-xylose). However, D-glucose as well as β-glucan were found to be in the highest amount in CAP. The helical structure was determined by Congo red assay which indicated that polysaccharides were in aggregate forms except HWP which consisted of tertiary structure. These diverse structural features may have imparted effect on free radical scavenging activity of polysaccharides where HWP was the most active in all assays. HWP was proved to be a good scavenger of free radicals, strong chelator of ferrous ion and had high reducing power. Thus it can be inferred that HWP may foster further studies for searching active compound which might be used as ingredients of functional foods, nutraceuticals and pharmaceuticals. Moreover, to the best of our knowledge this is the first report on chemical composition and antioxidant activity of different crude polysaccharides from M. gigantea.